High-weather-resistance two-component fast-curing photovoltaic sealant
By introducing trialkoxy ethylene-terminated polydimethylsiloxane into photovoltaic sealant formulation, the existing photovoltaic sealant cannot meet the long-term bonding strength in large-size photovoltaic modules and harsh outdoor environments. and the problem of aging resistance, achieving higher weather resistance and service life.
Patent Information
- Application Number
- CN202411505457.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-14
AI Technical Summary
Existing photovoltaic sealants cannot meet the long-term bonding strength and aging resistance requirements in large-size photovoltaic modules and harsh outdoor environments.
Develop a high weathering two-component rapid curing photovoltaic sealant, which enhances the high temperature and resistance of the sealant by introducing trialkoxy siliconeethylene terminal blocked polydimethylsiloxane into traditional silicone sealant formulations High humidity aging performance.
It significantly improves the overall aging resistance of the sealant, ensuring that the photovoltaic modules maintain good performance and long service life in harsh environments.
Smart Images

Figure BDA0005103825160000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a highly weather-resistant two-component fast-curing photovoltaic sealant. Background Art
[0002] When operating outdoors, photovoltaic modules inevitably face a variety of extreme weather conditions, including dramatic temperature fluctuations, high temperatures and humidity, strong winds, and the weight of snow. These harsh outdoor environments place extremely high demands on the performance and lifespan of photovoltaic modules. To ensure stable operation under these harsh conditions, photovoltaic modules must possess excellent mechanical stability and long-term weather resistance.
[0003] PV sealants play a crucial role in the construction of photovoltaic modules. They are primarily used to seal and bond the module frame to the laminate, ensuring the module's mechanical integrity and resistance to external environmental hazards. Therefore, PV sealants must possess excellent bonding properties and outstanding aging resistance to withstand long-term outdoor exposure.
[0004] Currently, silicone sealants are the most widely used photovoltaic sealants on the market. The high-energy silicon-oxygen bonds in their backbone make them superior to other sealing materials in terms of aging resistance. In a double-85 accelerated aging test, silicone sealants typically retain around 60% of their strength after 1000 hours, a performance level sufficient to meet the basic requirements of most photovoltaic modules.
[0005] However, with the continuous advancement and innovation of photovoltaic technology, the size of photovoltaic modules is becoming increasingly larger. This not only increases the requirements for the bonding strength of photovoltaic sealants, but also places higher standards on their aging resistance. While existing silicone sealants can provide sufficient bonding strength initially, their strength gradually decreases after long-term aging testing, making them unable to meet the long-term sealant strength requirements of large-sized photovoltaic modules. Therefore, the development and application of photovoltaic sealants with higher aging resistance has become particularly important to ensure the long-term stable and efficient operation of photovoltaic modules in the ever-expanding size and increasingly harsh outdoor environments. Summary of the Invention
[0006] The object of the present invention is to provide a highly weather-resistant two-component fast-curing photovoltaic sealant to solve the problems raised in the above-mentioned background technology.
[0007] To achieve the aforementioned objectives and meet the higher requirements for sealant aging resistance during long-term outdoor use of photovoltaic modules, the present invention provides a highly weather-resistant, two-component, fast-curing photovoltaic sealant. This sealant not only inherits the excellent performance of traditional silicone sealants but also further enhances their weather resistance. Through this improvement, the sealant can effectively protect photovoltaic modules, ensuring their excellent performance and long service life even in harsh outdoor environments.
[0008] The present invention provides the following technical solutions:
[0009] A highly weather-resistant two-component fast-curing photovoltaic sealant consists of a component A and a component B, wherein the mixing volume ratio of the components A and B is 1:1.
[0010] The component A is composed of the following components in parts by weight:
[0011] A1. 100 parts of α, ω-dihydroxy polydimethylsiloxane;
[0012] A2. 10-20 parts dimethyl silicone oil;
[0013] A3. 50 to 150 parts of reinforcing filler;
[0014] A4. Deep curing agent 0.1-2 parts;
[0015] The B component is composed of the following components in parts by weight:
[0016] B1. 100 parts of trialkoxysilylethylene-terminated polydimethylsiloxane;
[0017] B2. 50 to 150 parts of reinforcing filler;
[0018] B3. 15 to 50 parts of a cross-linking agent;
[0019] B4. 10 to 30 parts of a silane coupling agent;
[0020] B5. 0.1 to 2 parts of catalyst;
[0021] The A1 component is α,ω-dihydroxy polydimethylsiloxane, and its molecular structure is HO[(CH3)2SiO] n H, viscosity is 5000~50000mPa·s.
[0022] The A2 component is dimethyl silicone oil, and its molecular structure is (CH3)3SiO[(CH3)2SiO] n Si(CH3)3, viscosity is 100~1000mPa·s.
[0023] The A3 component is a reinforcing filler, which is selected from at least one of fumed silica, precipitated silica, nano calcium carbonate, silica powder, white corundum, and talc, or a combination of several fillers.
[0024] The A4 component is a deep curing agent and pure water is used.
[0025] The B1 component is a trialkoxysilylethylene terminated polydimethylsiloxane, and its molecular structure is (CH3O)3Si(CH2)2[(CH3)2SiO] n Si(CH2)2(CH3O)3, viscosity is 5000~80000mPa·s.
[0026] The B2 component is a reinforcing filler, which is selected from at least one of fumed silica, precipitated silica, nano calcium carbonate, silica powder, white corundum, and talc, or a combination of several fillers.
[0027] The B3 component is a crosslinking agent, which is selected from at least one of methyltrimethoxysilane, vinyltrimethoxysilane, methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate and partial hydrolyzates of the above crosslinking agents or a combination of several thereof.
[0028] The B4 component is a silane coupling agent, which is a reactant of one or more coupling agents selected from amino silane coupling agents, epoxy silane coupling agents, mercapto silane coupling agents, acrylate silane coupling agents, etc.
[0029] The B5 component is a catalyst, which is an organic tin or organic titanium catalyst, such as at least one of dibutyltin dilaurate, dibutyltin diacetate, dibutyltin oxide, tetra-tert-butyl titanate, tetraisobutyl titanate, and tetraisopropyl titanate.
[0030] The preparation method of component A comprises the following steps: adding components A1, A2 and A3 in the above-mentioned parts by weight into a stirred tank, dehydrating the mixture at 110-130° C. and a vacuum condition of -0.09 to -0.1 MPa for 2 to 4 hours, then cooling the mixture to 40° C., adding component A4, and stirring the mixture at a vacuum condition of -0.09 to -0.1 MPa for 10 minutes until the mixture is uniform and free of bubbles.
[0031] The preparation method of component B comprises the following steps: adding components B1 and B2 in the above-mentioned parts by weight into a stirring kettle, dehydrating for 2 to 4 hours under a vacuum condition of -0.09 to -0.1 MPa, then adding component B3, stirring for 10 minutes under a vacuum condition of -0.09 to -0.1 MPa, and finally adding components B4 and B5, stirring for 10 minutes under a vacuum condition of -0.09 to -0.1 MPa until the mixture is uniform and free of bubbles.
[0032] A highly weather-resistant two-component fast-curing photovoltaic sealant is prepared by mixing component A and component B in a volume ratio of 1:1 using a static mixing tube to obtain a finished product after uniform mixing.
[0033] In summary, due to the adoption of the above technology, the beneficial effects of the present invention are:
[0034] This invention introduces trialkoxysilylethylene-terminated polydimethylsiloxane into a conventional silicone sealant formula. This unique resin structure contains silylethylene groups, which exhibit excellent resistance to high-temperature and high-humidity aging. By incorporating this matrix resin into the cross-linked network of the silicone sealant, the overall aging resistance of the sealant can be significantly improved. This silicone sealant maintains improved stability and durability in high-temperature and high-humidity environments, thereby extending its service life and enhancing its reliability in photovoltaic module sealing. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] A highly weather-resistant two-component fast-curing photovoltaic sealant comprises a component A and a component B, wherein the mixing mass ratio of the components A and B is 1:1.
[0038] The component A is composed of the following components in parts by weight:
[0039] A1. 100 parts of α, ω-dihydroxy polydimethylsiloxane;
[0040] A2. 12 parts dimethyl silicone oil;
[0041] A3. 90 parts of reinforcing filler;
[0042] A4. 0.5 parts of deep curing agent;
[0043] The B component is composed of the following components in parts by weight:
[0044] B1. 100 parts of trialkoxysilylethylene-terminated polydimethylsiloxane;
[0045] B2. 110 parts of reinforcing filler;
[0046] B3. 40 parts of a cross-linking agent;
[0047] B4. 15 parts of silane coupling agent;
[0048] B5. 0.2 parts of catalyst;
[0049] The A1 component is α,ω-dihydroxy polydimethylsiloxane, and its molecular structure is HO[(CH3)2SiO] n H, viscosity is 50000 mPa·s.
[0050] The A2 component is dimethyl silicone oil, and its molecular structure is (CH3)3SiO[(CH3)2SiO] n Si(CH3)3, viscosity is 1000mPa·s.
[0051] The A3 component is a reinforcing filler, and nano calcium carbonate is selected.
[0052] The A4 component is a deep curing agent and pure water is used.
[0053] The B1 component is a trialkoxysilylethylene terminated polydimethylsiloxane, and its molecular structure is (CH3O)3Si(CH2)2[(CH3)2SiO] n Si(CH2)2(CH3O)3, viscosity is 10000mPa·s.
[0054] The B2 component is a reinforcing filler, and nano calcium carbonate is selected.
[0055] The B3 component is a cross-linking agent, and methyltrimethoxysilane is selected.
[0056] The B4 component is a silane coupling agent, and aminopropyltriethoxysilane is selected.
[0057] The B5 component is a catalyst, and dibutyltin dilaurate is selected.
[0058] The preparation method of component A comprises the following steps: adding components A1, A2 and A3 in the above-mentioned parts by weight into a stirred tank, dehydrating at 110° C. and -0.09 MPa vacuum conditions for 2 hours, then cooling to 40° C. and adding component A4, and stirring at -0.09 MPa vacuum conditions for 10 minutes until the mixture is uniform and free of bubbles.
[0059] The preparation method of the B component comprises the following steps: adding the above-mentioned components B1 and B2 in parts by weight into a stirred tank, dehydrating the mixture under a vacuum condition of -0.09 MPa for 2 hours, then adding the B3 component, stirring the mixture under a vacuum condition of -0.09 MPa for 10 minutes, and finally adding the B4 and B5 components, stirring the mixture under a vacuum condition of -0.09 MPa for 10 minutes until the mixture is uniform and free of bubbles.
[0060] Example 2
[0061] A highly weather-resistant two-component fast-curing photovoltaic sealant comprises a component A and a component B, wherein the mixing mass ratio of the components A and B is 1:1.
[0062] The component A is composed of the following components in parts by weight:
[0063] A1. 100 parts of α, ω-dihydroxy polydimethylsiloxane;
[0064] A2. 17 parts dimethyl silicone oil;
[0065] A3. 130 parts of reinforcing filler;
[0066] A4. 0.5 parts of deep curing agent;
[0067] The B component is composed of the following components in parts by weight:
[0068] B1. 100 parts of trialkoxysilylethylene-terminated polydimethylsiloxane;
[0069] B2. 110 parts of reinforcing filler;
[0070] B3. 30 parts of cross-linking agent;
[0071] B4. 15 parts of silane coupling agent;
[0072] B5. 0.15 parts of catalyst;
[0073] The A1 component is α,ω-dihydroxy polydimethylsiloxane, and its molecular structure is HO[(CH3)2SiO] n H, viscosity is 5000 mPa·s.
[0074] The A2 component is dimethyl silicone oil, and its molecular structure is (CH3)3SiO[(CH3)2SiO] n Si(CH3)3, viscosity is 350mPa·s.
[0075] The A3 component is a reinforcing filler and is selected from silicon micropowder.
[0076] The A4 component is a deep curing agent and pure water is used.
[0077] The B1 component is a trialkoxysilylethylene terminated polydimethylsiloxane, and its molecular structure is (CH3O)3Si(CH2)2[(CH3)2SiO] n Si(CH2)2(CH3O)3, viscosity is 80000mPa·s.
[0078] The B2 component is a reinforcing filler, and nano calcium carbonate is selected.
[0079] The B3 component is a cross-linking agent, and propyl orthosilicate is selected.
[0080] The B4 component is aminopropyltrimethoxysilane.
[0081] The B5 component is a catalyst, and dibutyltin oxide is selected.
[0082] The preparation method of component A comprises the following steps: adding components A1, A2 and A3 in the above-mentioned parts by weight into a stirred tank, dehydrating at 130° C. and -0.1 MPa vacuum conditions for 4 hours, then cooling to 40° C. and adding component A4, and stirring at -0.1 MPa vacuum conditions for 10 minutes until the mixture is uniform and free of bubbles.
[0083] The preparation method of the B component comprises the following steps: adding the above-mentioned components B1 and B2 in parts by weight into a stirred tank, dehydrating the mixture under a vacuum condition of -0.1 MPa for 4 hours, then adding the B3 component, stirring the mixture under a vacuum condition of -0.1 MPa for 10 minutes, and finally adding the B4 and B5 components, stirring the mixture under a vacuum condition of -0.1 MPa for 10 minutes until the mixture is uniform and free of bubbles.
[0084] Example 3
[0085] A highly weather-resistant two-component fast-curing photovoltaic sealant comprises a component A and a component B, wherein the mixing mass ratio of the components A and B is 1:1.
[0086] The component A is composed of the following components in parts by weight:
[0087] A1. 100 parts of α, ω-dihydroxy polydimethylsiloxane;
[0088] A2. 15 parts of dimethyl silicone oil;
[0089] A3. 120 parts of reinforcing filler;
[0090] A4. 0.3 parts of deep curing agent;
[0091] The B component is composed of the following components in parts by weight:
[0092] B1. 100 parts of trialkoxysilylethylene-terminated polydimethylsiloxane;
[0093] B2. 100 parts of reinforcing filler;
[0094] B3. 40 parts of a cross-linking agent;
[0095] B4. 12 parts of silane coupling agent;
[0096] B5. 0.2 parts of catalyst;
[0097] The A1 component is α,ω-dihydroxy polydimethylsiloxane, and its molecular structure is HO[(CH3)2SiO] n H, viscosity is 5000 mPa·s.
[0098] The A2 component is dimethyl silicone oil, and its molecular structure is (CH3)3SiO[(CH3)2SiO] n Si(CH3)3, viscosity is 100mPa·s.
[0099] The A3 component is a reinforcing filler, which is made of nano calcium carbonate and precipitated silica, and the mass ratio of the two fillers is 5:1.
[0100] The A4 component is a deep curing agent and pure water is used.
[0101] The B1 component is a trialkoxysilylethylene terminated polydimethylsiloxane, and its molecular structure is (CH3O)3Si(CH2)2[(CH3)2SiO] n Si(CH2)2(CH3O)3, viscosity is 50000mPa·s.
[0102] The B2 component is a reinforcing filler and is selected from white corundum.
[0103] The B3 component is a crosslinking agent, and vinyltrimethoxysilane is selected.
[0104] The B4 component is aminopropyltrimethoxysilane.
[0105] The B5 component is a catalyst, and dibutyltin diacetate is selected.
[0106] The preparation method of component A comprises the following steps: adding components A1, A2 and A3 in the above-mentioned parts by weight into a stirred tank, dehydrating at 130° C. and -0.1 MPa vacuum conditions for 4 hours, then cooling to 40° C. and adding component A4, and stirring at -0.1 MPa vacuum conditions for 10 minutes until the mixture is uniform and free of bubbles.
[0107] The preparation method of the B component comprises the following steps: adding the above-mentioned components B1 and B2 in parts by weight into a stirred tank, dehydrating the mixture under a vacuum condition of -0.1 MPa for 4 hours, then adding the B3 component, stirring the mixture under a vacuum condition of -0.1 MPa for 10 minutes, and finally adding the B4 and B5 components, stirring the mixture under a vacuum condition of -0.1 MPa for 10 minutes until the mixture is uniform and free of bubbles.
[0108] Example 4
[0109] A highly weather-resistant two-component fast-curing photovoltaic sealant comprises a component A and a component B, wherein the mixing mass ratio of the components A and B is 1:1.
[0110] The component A is composed of the following components in parts by weight:
[0111] A1. 100 parts of α, ω-dihydroxy polydimethylsiloxane;
[0112] A2. 18 parts dimethyl silicone oil;
[0113] A3. 100 parts of reinforcing filler;
[0114] A4. 0.4 parts of deep curing agent;
[0115] The B component is composed of the following components in parts by weight:
[0116] B1. 100 parts of trialkoxysilylethylene-terminated polydimethylsiloxane;
[0117] B2. 90 parts of reinforcing filler;
[0118] B3. 45 parts of a cross-linking agent;
[0119] B4. 12 parts of silane coupling agent;
[0120] B5. 0.3 parts of catalyst;
[0121] The A1 component is α,ω-dihydroxy polydimethylsiloxane, and its molecular structure is HO[(CH3)2SiO] n H, viscosity is 8000 mPa·s.
[0122] The A2 component is dimethyl silicone oil, and its molecular structure is (CH3)3SiO[(CH3)2SiO] n Si(CH3)3, viscosity is 500mPa·s.
[0123] The A3 component is a reinforcing filler, which is made of silica powder and fumed silica, with the ratio of the two fillers being 9:1.
[0124] The A4 component is a deep curing agent and pure water is used.
[0125] The B1 component is a trialkoxysilylethylene terminated polydimethylsiloxane, and its molecular structure is (CH3O)3Si(CH2)2[(CH3)2SiO] n Si(CH2)2(CH3O)3, viscosity is 80000mPa·s.
[0126] The B2 component is a reinforcing filler and is talcum powder.
[0127] The B3 component is a cross-linking agent, and propyl orthosilicate is selected.
[0128] The B4 component is N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
[0129] The B5 component is a catalyst, and dibutyltin dilaurate is selected.
[0130] The preparation method of component A comprises the following steps: adding components A1, A2 and A3 in the above-mentioned parts by weight into a stirred tank, dehydrating at 130° C. and -0.1 MPa vacuum conditions for 4 hours, then cooling to 40° C. and adding component A4, and stirring at -0.1 MPa vacuum conditions for 10 minutes until the mixture is uniform and free of bubbles.
[0131] The preparation method of the B component comprises the following steps: adding the above-mentioned components B1 and B2 in parts by weight into a stirred tank, dehydrating the mixture under a vacuum condition of -0.1 MPa for 4 hours, then adding the B3 component, stirring the mixture under a vacuum condition of -0.1 MPa for 10 minutes, and finally adding the B4 and B5 components, stirring the mixture under a vacuum condition of -0.1 MPa for 10 minutes until the mixture is uniform and free of bubbles.
[0132] The highly weather-resistant two-component fast-curing photovoltaic sealant prepared in Example 1 has the following performance indicators:
[0133]
[0134] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.
[0135] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.
Claims
1. A highly weather-resistant two-component fast-curing photovoltaic sealant, characterized in that: The sealant is composed of component A and component B, and the mixing mass ratio of component A to component B is 1:1: The component A is composed of the following components by weight: A1. 100 parts of α, ω-dihydroxy polydimethylsiloxane; A2. 10-20 parts of dimethyl silicone oil; A3. 50 to 150 parts of reinforcing filler; A4. Deep curing agent 0.1-2 parts; The B component is composed of the following components by weight: B1. 100 parts of trialkoxysilylethylene terminated polydimethylsiloxane; B2. 50 to 150 parts of reinforcing filler; B3. 15 to 50 parts of a cross-linking agent; B4. 10 to 30 parts of silane coupling agent; B5. 0.1 to 2 parts of catalyst.
2. A highly weather-resistant two-component fast-curing photovoltaic sealant according to claim 1, characterized in that: The A1 component is α, ω-dihydroxy polydimethylsiloxane, and its molecular structure is HO[(CH3)2SiO] n H, viscosity is 5000~50000mpa·s.
3. A highly weather-resistant two-component fast-curing photovoltaic sealant according to claim 1, characterized in that: The A2 component is dimethyl silicone oil, and its molecular structure is (CH3)3SiO[(CH3)2SiO] n Si(CH3)3, viscosity is 100~1000mPa·s.
4. A highly weather-resistant two-component fast-curing photovoltaic sealant according to claim 1, characterized in that: The A3 component is a reinforcing filler, which is selected from at least one of fumed silica, precipitated silica, nano calcium carbonate, silica powder, white corundum, and talcum powder, or a combination of several fillers; The A4 component is a deep curing agent, and pure water is selected.
5. A highly weather-resistant two-component fast-curing photovoltaic sealant according to claim 1, characterized in that: The B1 component is a trialkoxysilylethylene terminated polydimethylsiloxane, and its molecular structure is (CH3O)3Si(CH2)2[(CH3)2SiO] n Si(CH2)2(CH3O)3, viscosity is 5000~80000mPa·s.
6. A highly weather-resistant two-component fast-curing photovoltaic sealant according to claim 1, characterized in that: The B2 component is a reinforcing filler, which is selected from at least one of fumed silica, precipitated silica, nano calcium carbonate, silica powder, white corundum, and talcum powder, or a combination of several fillers; The B3 component is a crosslinking agent, which is selected from at least one of methyltrimethoxysilane, vinyltrimethoxysilane, methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate and partial hydrolyzates of the above crosslinking agents or a combination of several thereof; The B4 component is a silane coupling agent, which is a reactant of one or more coupling agents selected from amino silane coupling agents, epoxy silane coupling agents, mercapto silane coupling agents, acrylate silane coupling agents, etc.; The B5 component is a catalyst, which is an organic tin or organic titanium catalyst, such as at least one of dibutyltin dilaurate, dibutyltin diacetate, dibutyltin oxide, tetra-tert-butyl titanate, tetraisobutyl titanate, and tetraisopropyl titanate.
7. A highly weather-resistant two-component fast-curing photovoltaic sealant according to claim 1, characterized in that: The preparation method of component A comprises the following steps: adding components A1, A2 and A3 in the above-mentioned weight proportions into a stirring kettle, dehydrating for 2 to 4 hours at 110 to 130° C. and -0.09 to -0.1 MPa vacuum conditions, then cooling to 40° C., adding component A4, and stirring for 10 minutes at -0.09 to -0.1 MPa vacuum conditions until the mixture is uniform and free of bubbles.
8. A highly weather-resistant two-component fast-curing photovoltaic sealant according to claim 1, characterized in that: The preparation method of component B comprises the following steps: adding components B1 and B2 in the above-mentioned weight proportions into a stirring kettle, dehydrating for 2 to 4 hours under a vacuum condition of -0.09 to -0.1 MPa, then adding component B3, stirring for 10 minutes under a vacuum condition of -0.09 to -0.1 MPa, and finally adding components B4 and B5, stirring for 10 minutes under a vacuum condition of -0.09 to -0.1 MPa until the mixture is uniform and free of bubbles.